Faktor-Faktor Yang Mempengaruhi Keputusan Berkunjung Di Bird Park Palembang - Hendry, Kelvin; Widagdo, Herry (MDP Student Conference, 2024)
The aim of this research is to determine the influence of accessibility and facilities on the decision to visit Bird Park Palembang recreational tourism. Data collection for this research distributed questionnaires to 382 respondents. Sampling used nonprobability sampling with a purposive sampling method with the help of SPSS 21. Partial test results show that Accessibility and Facilities have a significant positive effect on the decision to visit with a value of 0.000 < 0.05. The simultaneous test proves that the F value is 95.160 with a significant value of 0.000, which means that the variables of attractions and amenities can be said to have a positive and significant effect on interest in visiting.